River damming enhances ecological functional stability of planktonic microorganisms - Li, Wanzhu; Wang, Baoli; Liu, Na; Yang, Meiling; Liu, Cong-Qiang; Xu, Sheng (Frontiers in Microbiology, 2022)
Planktonic microorganisms play an important role in maintaining the ecological functions in aquatic ecosystems, but how their structure and function interrelate and respond to environmental changes is still not very clear. Damming interrupts the river continuum and alters river nutrient biogeochemical cycling and biological succession. Considering that river damming decreases the irregular hydrological fluctuation, we hypothesized that it can enhance the ecological functional stability (EFS) of planktonic microorganisms. Therefore, the community composition of planktonic bacteria and archaea, functional genes related to carbon, nitrogen, sulfur, and phosphorus cycling, and relevant environmental factors of four cascade reservoirs in the Pearl River, Southern China, were investigated to understand the impact of damming on microbial community structure and function and verify the above hypothesis. Here, the ratio of function to taxa (F:T) based on Euclidean distance matrix analysis was first proposed to characterize the microbial EFS; the smaller the ratio, the more stable the ecological functions. The results showed that the reservoirs created by river damming had seasonal thermal and chemical stratifications with an increasing hydraulic retention time, which significantly changed the microbial structure and function. The river microbial F:T was significantly higher than that of the reservoirs, indicating that river damming enhances the EFS of the planktonic microorganisms. Structural equation modeling demonstrated that water temperature was an important factor influencing the relationship between the microbial structure and function and thus affected their EFS. In addition, reservoir hydraulic load was found a main factor regulating the seasonal difference in microbial EFS among the reservoirs. This study will help to deepen the understanding of the relationship between microbial structure and function and provide a theoretical basis of assessing the ecological function change after the construction of river damming.